Analisis Pengujian Elastisitas Young Modulus Pada Wood Poylmer Composite Dengan Metode Hot Press - Bagus Suranta Sembiring; Yopan Rahmad Aldori; Ari Handoko (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
This study aims to determine the Elasticity of Wood Polymer Composite (WPC). The composite was made using 15 grams of wood powder and 30 grams of plastic sheets, processed for 60 minutes at a pressure of 8 MPa. The temperature used was 125°C. The hot press method is one of the techniques commonly used to produce WPC. In this process, a mixture of wood fibre and plastic sheets is heated and pressurised below the temperature to compact and form the composite according to the desired mould. By creating a dogbone-shaped specimen with a distinctive shape, featuring a narrowed centre, the design is intended to ensure that failure occurs at the centre of the specimen when tested, thereby providing more accurate results about the material's strength.